Transformational leadership and its role in organizational success An analytical study of the views of a sample of employees at the Faculty of Education, Samarra University - حمدان, اسحق يوسف (Journal of Economics and Administrative Sciences, 2019)
This research aims to know the role of transformational leadership in the organizational success of the College of Education at Samarra University. The researcher adopted the analytical descriptive method in analyzing the research problem. The research included two main hypotheses that resulted in four hypotheses that were subjected to statistical tests. A sample of (54) The researcher used the survey method as a main tool for collecting data and information as well as visits and structured interviews that took place during the period of application. The research reached a set of conclusions and recommendations among the conclusions that there is an art relationship There is a strong and moral impact between transformational leadership and organizational success at the macro and sub-level, as well as the managerial leadership with the qualities of transformational leadership at a good level with its commitment to increasing efficiency and organizational effectiveness. The most prominent recommendations were the need for the management of the faculty to be aware of the importance of individual consideration and intellectual To gain their employees' confidence in creativity and commitment in their work, which has an impact on increasing efficiency and organizational effectiveness, and the need to pay more attention to organizational efficiency as it is the fundamental basis for organizational success and that the focus on organizational effectiveness can not To reach the college in question to high levels of organizational success